The association of triglyceride glucose waist-to-height ratio index with depression in United States adults - Zhang, Rangrang; Li, Nanfang; Zhang, Delian; Wang, Menghui; Tuerhong, Reziya; Luo, Qin (Frontiers in Nutrition, 2025)
ObjectiveThe purpose of this study is to investigate the relationship between the triglyceride glucose waist-to-height ratio (TyG-WHtR) and depression.MethodsData were used from the National Health and Nutrition Examination Survey (NHANES) that was conducted between 2005 and 2018, which included 15,630 eligible people. Based on a Patient Health Questionnaire (PHQ) score of more than 10, the participants were each assigned to one of the two groups: a group of depressed individuals (n = 1,347) and a group of non-depressed individuals (n = 14,283). To investigate the connection between TyG-WHtR and depression, one-way comparative analyses and multifactorial logistic regression were carried out, and subgroup analyses were also used. To do more research into this connection, quartile grouping was used, and restricted cubic spline (RCS) curves were utilized to evaluate the patterns that emerged in the relationship between TyG-WHtR and depression.ResultsAn independent and substantial positive correlation between TyG-WHtR and depression was found by multifactorial logistic regression of the data. In the fully corrected model, TyG-WHtR levels were associated with a higher prevalence of depression (OR = 1.19, 95%:1.09–1.29). Analysis of TyG-WHtR quartiles showed a significant trend in Q4 compared to Q1 (trend p < 0.001). There is a linear connection between TyG-WHtR and depression. From the RCS curve, we can see that its threshold is 5.07. From the ROC curve, we know that the predictive value of TyG-WHtR is higher than that of body mass index (BMI). Subgroup analyses indicated significant interactions with diabetes, marital status, education, and BMI.ConclusionDepressive symptoms are significantly associated with TyG-WHtR, which is a strong positive correlation. This index may provide useful insights into the diagnosis and treatment of depression as related research continues to advance.